Diversity, equity, and inclusion in cancer clinical trial enrollment: Laying the groundwork for a cancer center collaborative intervention through key informant interviews. Issue 28 (1st October 2022) - Goel, Pakhi; Edmonds, Megan C.; Lin, Sylvia; Goodman, Karyn A.; Smith, Cardinale B.; Hillyer, Grace C.; Bickell, Nina A.
Abstract : 98 Background: Clinical trial (CT) participation rates in the US are about 8% overall. Although, Black, Indigenous and People of Color (BIPOC) are as willing to join CTs as Whites, they remain underrepresented. We will implement a multi-level intervention across 3 cancer centers in New York City by creating a collaborative pool of CTs for breast, prostate, and liver cancer, thereby increasing availability of trials for all, especially BIPOC populations. To lay the groundwork, we conducted a formative evaluation to identify constructs that can influence implementation of this intervention. Methods: We designed a semi-structured interview guide for key informants to ascertain barriers and facilitators of enrollment at 1 cancer center and its 2 community affiliates. 23 key informants including oncologists, research staff, informatics, nurses, and cancer center leadership were identified using a targeted approach, followed by snowball sampling. Interviews were recorded, transcribed, and analyzed using thematic analysis approach. Results: Facilitators of accrual include patient referrals from physician-investigators and their teams, and oncologists' knowledge of open trials through tumor boards, disease focus groups, and research meetings. Major barriers to CT enrollment are gaps in trial portfolio, inadequate infrastructure (e.g., staffing, space, and time), and incentives (e.g., RVU-based reimbursements). Informants felt that for patients, financial toxicity, medical mistrust, inadequate health literacy, comorbidities, poor performance status, and language are reasons for low accrual. Physicians emphasized their willingness to refer patients out-of-institution for CTs but lacked knowledge of outside trials. Care coordination across sites and loss of revenue for home institution are system-level barriers to referral. Additionally, informants believed that patients' willingness to seek trials at other institutions is influenced by their commute, unfamiliarity with a new system, insurance coverage, rapport with oncologist, and motivation. Conclusions: Involving key stakeholders, increasing physician awareness of open CTs, educating patients and addressing their concerns about CTs, improving access to bilingual materials and interpreters, standardizing care coordination and ensuring similar rates of referrals across institutions are key facilitators to implement a multi-level intervention to increase CT enrollment across a cancer center collaboration.